2006
DOI: 10.1002/jcb.20887
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear addressing provides a clue for the transforming activity of amino‐truncated CCN3 proteins

Abstract: CCN3 is a founding member of the CCN (Cyr61, Ctgf, Nov) family of cell growth and differentiation regulators. These secreted proteins are key regulators in embryonic development, and are associated with severe pathologies including fibrotic diseases and cancers. CCN3 was discovered as a MAV integration site in an avian nephroblastoma. Previous work established that the amino-truncated protein expressed in this tumor was inducing morphological transformation of chicken embryo fibroblasts, whereas the full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
78
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 37 publications
(61 reference statements)
6
78
0
Order By: Relevance
“…Although we did not study the short form at the functional level, its nuclear localization in melanoma cells (Fig. 3A and C) is consistent with other studies and with its regulatory effect on transcription (29). Our results do, however, clearly show that the CCN3 fulllength protein is associated with high adhesiveness of melanoma cells to ECM proteins.…”
Section: Discussionsupporting
confidence: 89%
“…Although we did not study the short form at the functional level, its nuclear localization in melanoma cells (Fig. 3A and C) is consistent with other studies and with its regulatory effect on transcription (29). Our results do, however, clearly show that the CCN3 fulllength protein is associated with high adhesiveness of melanoma cells to ECM proteins.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we may speculate that CCN3 may be directly inhibiting the transcription of CCN2 and CCN4 genes. It is reported that CCN3 is present in the nucleus and behaves like a transcription factor therein (Planque et al 2006). Of our interest, CCN5, another CCN family member, actually regulates gene expression in the nucleus (Sabbah et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These four domains have been shown to be discrete structural entities and can be produced as individual truncates that still possess biological activity (24). The CCN family is highly conserved at the primary structure level with ϳ30 -50% amino acid identity (and 40 -60% similarity) (28,29). CCN5 is an exception in that it lacks the CT domain but still maintains the first three highly conserved domains, and CCN6 lacks four normally conserved cysteine residues in the VWC domain.…”
mentioning
confidence: 99%